Mortality due to oral and oropharyngeal cancer in Uruguay from 1997 to 2014 - Maria Laura Cosetti-Olivera; Amanda Ramos da Cunha; Taiane Schaedler Prass; Marco Antonio Trevizani Martins; Fernando Neves Hugo; Manoela Domingues Martins (University of São Paulo, 2019)
Abstract Oral and oropharyngeal cancer is considered a public health problem in several countries due to its high incidence and mortality rate. Objective: This study aimed to analyze oral and oropharyngeal cancer mortality in Uruguay from 1997 to 2014 by age, sex and country region. Methodology: A time series ecological study using secondary data was performed. Data on mortality due to oral and oropharyngeal cancers were obtained from the Vital Statistics Department of Uruguay's Ministry of Public Health. Results: The cumulative mortality rate due to oral and oropharyngeal cancer over the study period was of 19.26/100,000 persons in women and 83.61/100.000 in men, with a mean annual rate of 1.75/100,000 in women and 7.60/100,000 in men. Mortality rate from both sites during the study period was 4.34 times higher in men than in women. Malignant neoplasms of other parts of the tongue and base of tongue showed the highest mortality rate. The means of the annual coefficients of deaths were higher for the age groups between 50 and 69 years. Higher mortality rates of oral and oropharyngeal cancer were observed in Artigas (4.63) and Cerro Largo (3.75). Conclusions: Our study described a high mortality rate for oral and oropharyngeal cancer in Uruguay from 1997 to 2014. According to the country's health department, men, tongue cancer, and oral cavity had higher mortality rates, with some variation. Prevention strategies with control of risk factors and early diagnosis are necessary to improve survival in the Uruguayan population.